Extraplanar ultrasound-guided multi-tract percutaneous nephrolithotomy: a retrospective comparative study in patients with complex nephrolithiasis - Wei, Geng-Geng; Kwan, Kristine J. S.; Yang, Yu; Yang, Qing-Shan; Lu, Zhen-Quan; Xiong, Lin; Xu, Xiang (Frontiers in Urology, 2026)
PurposeThis study aimed to compare the efficacy and safety of extraplanar ultrasound (USG) guidance with the conventional technique in multi-tract percutaneous nephrolithotomy (PCNL) for managing complex renal stones (CRS).Materials and methodsA retrospective analysis was conducted on 91 patients diagnosed with CRS treated with multi-tract PCNL between May 2017 and December 2020. Patients were divided into the conventional USG group and the extraplanar USG group. Patient demographics and operative characteristics were compared, acknowledging the baseline stone size imbalance as a potential confounder.ResultsFifty-one (56.0%) patients received extraplanar USG-guided PCNL. The median maximum stone diameter in the conventional group was significantly larger (30 vs. 22 mm, p = 0.001). All tracts were established successfully. Despite larger stones, the conventional group had significantly longer operative times (145 vs. 108 min, p = 0.001). No significant difference was observed in stone-free rates (55% vs. 57%). The extraplanar group showed significantly lower postoperative serum creatinine levels (80 vs. 87 μmol/L, p = 0.03) and shorter hospital stays (8 vs. 10 days, p = 0.01). Postoperative fever occurred in four patients in the extraplanar group (8% vs. 0%, p = 0.07).ConclusionsMulti-tract PCNL performed under extraplanar USG guidance is safe and efficacious for CRS management. The technique optimizes the puncture strategy, offering superior operative efficiency and potential nephron preservation despite baseline stone load differences.